The Theme and Effective Factors in the Transformation and Development of «Swastika» Motif in Iranian Art from Ancient to Seljuk Period - Mohamad Motevalli; Khashayar Ghazizadeh; Morteza Afshari (پیکره)
Introduction: One of the oldest geometric motifs of the ancient world is a motif created from two crossed lines - a cross with broken arms or a ninety-degree angle. In international sources, this motif is known as «Swastika» with the concept of well-being, and in Persian sources, it is known as «Gardune-e Khorshid» and «Mehrane». Researchers consider the origin of this motif to be ancient civilizations such as the Indus Valley, Egypt, China, Mesopotamia, and the Aryan peoples, who, despite different names, have a similar formal structure. In Iran, this motif was depicted on pottery for the first time since the fifth millennium B.C., and its continued use can be seen until the beginning of the Islamic period. Identifying the theme and factors of drawing the Swastika in Iranian art and showing its evolution and development from the point of view of form and content in pre-Islamic Iranian art until the early Islamic era is one goal of the present study. In this regard, the questions of how the form and content of the Swastika have evolved in Iranian art from the ancient period to the Seljuk period and the common and distinctive factors of its drawing in the pre-Islamic and Islamic periods are addressed.Research Method: The current research used descriptive-analytical and historical approaches. The data collection was conducted using library- and field-based methods. The statistical population included 29 samples from the pre-Islamic and Islamic periods with distinctive and distinctive characteristics that show the evolution of the Swastika.Findings: The presence of religion, especially the worship of Gods, burial rites and Mithraism in ancient Iran, was one of the essential reasons for drawing the Swastika, and for this reason, it is known as the «Gardune-e Mehr». Astronomical motifs such as twelve constellations and folk beliefs such as good luck, avoiding the evil eye, and being safe from calamity have been influential in representing this motif in both the pre-Islamic and Islamic periods. In Islamic art, this motif is a symbol of light and, accordingly, God. Besides displaying its original form during this period, in some works, it has become «Solomon's knot» and «Shamseh» by combining curved forms and plant motifs.Conclusion: The Swastika has been a sacred symbol in Iranian art from the ancient period to the early Islamic period and often served ancient myths and religions. In the early period, this motif symbolized the God and Goddesses of the Sun and was gradually associated with the ritual symbols of Mithraism and Zoroastrianism in works of art. In the Islamic period, this motif underwent metamorphosis and was used as a symbol of God and Islamic holy persons.